Mindfulness-based intervention in adolescents at risk for excess weight gain: 1.5-year follow-up of pilot randomized controlled trial. (December 2021) - Bernstein, Ruth; Sanchez, Natalia; Clark, Emma L.M.; Conte, Isabella; Gulley, Lauren D.; Legget, Kristina T.; Cornier, Marc-Andre; Melby, Christopher; Johnson, Sarah A.; Lucas-Thompson, Rachel; Shomaker, Lauren B.
Abstract: Background: Mindfulness-based intervention (MBI) may offer a novel means of preventing excess weight gain in adolescents, theoretically by decreasing stress-eating through altering executive functioning (EF) and food-reward sensitivity. Methods: N = 54 12–17y girls and boys at-risk for excess weight gain (i.e., BMI ≥70th percentile or two biological parents with reported obesity [BMI ≥30 kg/m 2 ]) participated in a 1.5-year follow-up of a pilot randomized controlled trial comparing 6-week/6-session MBI ( n = 29) and a health education (HE) control ( n = 25). Laboratory stress-eating, food-reward sensitivity, EF, perceived stress, and BMI/adiposity were re-assessed at 1.5-years with validated measures. Changes from baseline to 1.5-year follow-up were explored with ANCOVA, accounting for the respective baseline outcome, age, and sex. Results: Compared to MBI (M = −21, SE = 59), HE had greater increases in stress-eating from baseline to 1.5-years (M = 194, SE = 63, Cohen's d = 0.59, p = .01). There were no other between-condition differences. Discussion: MBI may prevent worsening stress-eating for adolescents at-risk for excess weight gain. The potential for MBI as an intervention for stress-eating and ultimately, weight stabilization warrants testing in an adequately-powered trial. Highlights: Adolescents were assessed 1.5-years after a mindfulness-based intervention (MBI) Teens in MBI had less stress-eating than those in health education There were no other significant between-group effects